2015
DOI: 10.17219/acem/29181
|View full text |Cite
|
Sign up to set email alerts
|

C4d Deposition Reveals Myocardial Infarction After Cardiac Arrest -Experimental Study

Abstract: Background. The diagnosis of regional myocardial infarction (MI) after cardiac arrest and ischemia-reperfusion injury (IRI) is a major clinical challenge. Objectives. We evaluated in a rat cardiac transplantation model whether IRI alone or with MI would induce complement C4d deposition. Material and Methods. Isogenic heterotopic cardiac transplantation was performed in 16 Fischer 344 rats to induce IRI, of which 9 rats also underwent ligation of the left anterior coronary artery (LAD) of the heart to yield MI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The diagnostic criteria of acute myocardial infarction were as follows: CT angiography showed that dissection diaphragm divided aorta into true lumen and false lumen ( 3 ). The diagnostic criteria of coronary artery stenosis were the pathological expansion of abdominal aorta exceeding 50% of normal blood vessel diameter ( 12 ). All the patients underwent preoperative examination including ultrasonic cardiogram and signed informed consent after postoperative pathology identification.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criteria of acute myocardial infarction were as follows: CT angiography showed that dissection diaphragm divided aorta into true lumen and false lumen ( 3 ). The diagnostic criteria of coronary artery stenosis were the pathological expansion of abdominal aorta exceeding 50% of normal blood vessel diameter ( 12 ). All the patients underwent preoperative examination including ultrasonic cardiogram and signed informed consent after postoperative pathology identification.…”
Section: Methodsmentioning
confidence: 99%